2020
DOI: 10.3390/ijerph17113808
|View full text |Cite
|
Sign up to set email alerts
|

Social and Structural Determinants of Household Support for ART Adherence in Low- and Middle-Income Countries: A Systematic Review

Abstract: Adherence to HIV antiretroviral therapy (ART) is a crucial factor in health outcomes for people living with HIV (PLWH). Interventions to support ART adherence are increasingly focused on the household as a source of social support. This review aims to examine the social and structural determinants of support for ART adherence within households and families in low- and middle-income countries (LMICs). The review methodology followed the recommendations of the Preferred Reporting Items for Systematic Reviews and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 93 publications
3
15
1
Order By: Relevance
“…This was reflected in the comments of some PLHIV in Belu that explained about the encouragement, provision of traditional medicines or information about traditional treatment by extended families, neighbours and friends as factors that influenced their family’s decisions for the use of traditional medicines from traditional healers for HIV treatment. The findings add further evidence to a previous study’s findings [43] which have reported that social factors, such as gender norms, social status and stigma affected family support for PLHIV and their access to ART. In addition, evidence from the current study also demonstrates that the poor physical and health conditions of PLHIV, and their dependency on family support for their daily needs and healthcare influenced their ability to make decisions about their own health treatment, hence indulging family decisions for traditional treatment, which negatively affected their access to ART.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This was reflected in the comments of some PLHIV in Belu that explained about the encouragement, provision of traditional medicines or information about traditional treatment by extended families, neighbours and friends as factors that influenced their family’s decisions for the use of traditional medicines from traditional healers for HIV treatment. The findings add further evidence to a previous study’s findings [43] which have reported that social factors, such as gender norms, social status and stigma affected family support for PLHIV and their access to ART. In addition, evidence from the current study also demonstrates that the poor physical and health conditions of PLHIV, and their dependency on family support for their daily needs and healthcare influenced their ability to make decisions about their own health treatment, hence indulging family decisions for traditional treatment, which negatively affected their access to ART.…”
Section: Discussionsupporting
confidence: 87%
“…This was also reflected in the fact that access to HIV care services or ART was a last choice for participants (PLHIV), and this was made once traditional treatment was felt to be ineffective and their physical and health conditions were getting worse. These are not dissimilar to previous findings which reported insufficient or incorrect knowledge about ART as a barrier to the access and adherence to ART among PLHIV [41], and positive relationships between a lack of ART knowledge and less family support for ART access and adherence [43]. In other words, the current study indicates a lack of family support for PLHIV prior to or in the early stages of ART as a barrier to their access to HIV care services and ART initiation or adherence [39][40][41][42].…”
Section: Discussioncontrasting
confidence: 80%
“…Similarly, no evidence was found for an association between the education level of the respondent and ART adherence. This is in contrast to other studies in South Africa [ 88 90 ], however, assessing the relationship between ART adherence and factors such as education is notoriously complex given the multiple pathways between them [ 36 , 91 ], especially in times of crisis.…”
Section: Discussionmentioning
confidence: 79%
“…Public health approaches to ART adherence increasingly recognize the role that the immediate environment, and especially the household, play in creating health-enabling environments [ 31 36 ]. Masquillier et al posit that when household members enact behaviours supporting HIV prevention, discussion and disclosure, this ‘household HIV competency’ has positive effects on ART adherence for PLWH [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Predictors encompassed factors previously associated with ART adherence among ALWHIV [27]. These included: (1) demographic factors, that is age [28], gender [18]; (2) individual‐level psychosocial and HIV‐related factors, that is depression, hopelessness [29,30], adherence self‐efficacy [29], substance use [31], HIV disclosure [32] and history of ART adherence [33]; (3) household‐level factors, that is family cohesion [34], biological caregiver [28], HIV treatment supporter [28]; (4) community/structural‐level factors, that is social support network [34], distance to health facility [18], HIV‐related stigma [35]; asset ownership [18], child poverty [28], economic intervention assignment [36].…”
Section: Methodsmentioning
confidence: 99%